Agrobacterium rhizogenes-mediated transformation and its biotechnological applications in crops - (:unkn) unknown (Springer US, 2013)
The history of Agrobacterium-related plant biotechnology goes back for more than three decades with the discovery of molecular mechanisms of crown gall disease in plants. After 1980s, gene technologies began developing rapidly and today, related with the improved gene transfer methods, plant biotechnology has become one of the most important branches in science. Till now, the most important genes related with agricultural affairs have been utilized for cloning of plants with the deployment of different techniques used in genetic engineering. Especially, Agrobacterium tumefaciens was used extensively for transferring desired genetic materials to plants rapidly and effectively by the researchers to create transgenic plants. Recognition of the biology of Agrobacterium species and newly developed applications of their T-DNA systems has been a great step in plant biotechnology. This chapter provides the reader with extensive information on A. rhizogenes which is responsible for the development of hairy root disease in a wide range of dicotyledonous plants and its T-DNA system. This knowledge will be useful in improving utilization of crops and the formulation of new and up-graded transgenic based food products. © 2013 Springer Science+Business Media, LLC. All rights reserved.